Prevalence of dementia and its impact on mortality in patients with coronavirus disease 2019: A systematic review and meta‐analysis. Issue 2 (19th December 2020) - July, Julius; Pranata, Raymond
Abstract : Aim: In this systematic review and meta‐analysis, we aimed to evaluate the prevalence of dementia in patients with COVID‐19 and its association with mortality. We also aimed to discover whether age, sex and other comorbidities might affect the association between dementia and mortality. Methods: We carried out a systematic literature search using PubMed, SCOPUS, EuropePMC and the Cochrane Central Database. The outcome of interest was mortality, defined as clinically validated mortality/death/non‐survivor in the studies. The pooled effect estimates were presented as odds ratio and adjusted odds ratio. Results: A total of 56 577 patients from 10 studies were included. The prevalence of dementia in this pooled analysis was 10% (7–13%). Dementia was associated with increased mortality in both pooled unadjusted (odds ratio 2.80, 95% CI 1.85–4.24, P < 0.001; I 2 = 93.7%) and adjusted effect estimates (adjusted odds ratio 1.80, 95% CI 1.45–2.24, P < 0.001; I 2 = 72.9%). The association between dementia and mortality was influenced by age (coefficient −0.047, P < 0.001) and hypertension (coefficient −0.009, P = 0.020). Conclusions: This study showed that dementia was associated with increased mortality in COVID‐19 patients. The association was affected by age and comorbidities. Geriatr Gerontol Int 2021; 21: 172–177 .